PRIMARY EVALUATION OF FILTER CAKE BREAKER IN BIODEGRADABLE SYNTHETIC-BASED DRILL-IN-FLUID - Wayo, Dennis Delali Kwesi (Nazarbayev University School of Mining and Geosciences, 2022)
Filter cake breakers are the means to remove filter cakes from the walls of the wellbore before completion and production. During drilling, there are layers of filter cakes formed that can’t easily be penetrated; these layers prevent drilling fluids from invading the formation or an influx of the formation fluid into the wellbore; fending of blowouts. Chemical breakers are difficult to optimize, and finding a reliable way to remove filter cakes from the wellbore in a uniform manner had been a singular difficulty for researchers. Some good engineers and operators in the industry incorrectly analyze the flow of hydrocarbons into the wellbore, resulting in the designation of wells as redundant; this is due to the causes of layered filter cakes. The thesis study conducted a laboratory evaluation of several filter cake breakers using ethylene-diamine-tetra-acetic acid (EDTA), Silica dioxide (SiO2), Titanium dioxide (TiO2), and Graphene particles for better concentration optimization, and to determine how these organic acid and nanoparticles will react in a pressure, temperature regions. Also, the study formulated a biodegradable synthetic based mud drill-in-fluid (BSBMDIF) to create filter cakes using a replica of actual reservoir conditions. The methodology sought to formulate biodegradable synthetic based mud DIF which contained barite, bentonite, guar gum, caustic soda, calcium chloride, Sodium Tridecyl Ether Sulphate, graphene powder, water, and base oil, and the rheological parameters of the DIF were defined using an OFITE 900 viscometer, after which it passed the wellbore stability test. For the creation of filter cakes, HTHP filter press and Blue-M oven were utilized. Filter cakes build up in the BSBMDIF were subject to breakthrough, soaking, and injectivity tests, with the same amount of concentration measured in weights, the various filter cake breakers exhibited some level of efficiency. The organic acid, EDTA after treating filter cakes for 42 hours yielded an 80.98% efficiency, while the nanoparticles, especially Silica dioxide came close to reducing the weight of the filter cake by 69.13%. An increase in removal efficiency under this study was seen increasing the rate of return permeability, filter cakes that were treated with EDTA for 42 hours had a tremendous increase in return permeability by 74.89%, whiles graphene by contrast yielded slow permeability return by 52.97%. However, the nanoparticles under normal pressure and temperature maintained its physiochemical properties under a pressure of 100 to 500 psi and a temperature of 200℉.
Keywords: Filter Cake Thickness; Type of access: Open Access; Commercial Cake Breakers; Nanoparticles; Water-Based Muds; Biodegradable; Synthetic Based Muds; Silica and Graphene